International co-operation in combating cybercrime. Selected issues - Cieśla, Rafał (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The article discusses selected aspects of international co-operation in combating selected types of cybercrime. The complex character of criminal activity besetting contemporary banking causes numerous difficulties and poses many challenges, such as detecting and apprehending perpetrators. Online banking crime constitutes a specific category, comprising cashless transactions and electronic data processing. The specific environment of online banking, where crime is committed, determines the nature of traces left by perpetrators; it also necessitates creation of new forensic methods based on modern technology. The more sophisticated the crime, the more difficult it is to identify the perpetrators. Therefore, international co-operation in combating cybercrime is essential.
Keywords: cyberprzestępczość; współpraca międzynarodowa; dokument; dokument elektroniczny; wyłudzanie informacji